2017
DOI: 10.2903/j.efsa.2017.4991
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza

Abstract: Previous introductions of highly pathogenic avian influenza virus (HPAIV) to the EU were most likely via migratory wild birds. A mathematical model has been developed which indicated that virus amplification and spread may take place when wild bird populations of sufficient size within EU

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 353 publications
(522 reference statements)
0
52
0
Order By: Relevance
“…Nevertheless, the risk of AI viruses being transported to Europe through poultry trade is negligible as live poultry, day-old chicks and semen have been identified as the only non-wild bird pathways via which AI virus introduction is non-negligible, and as suitable risk management measures are in place, such as testing and quarantine (EFSA AHAW Panel et al, 2017). Nevertheless, the risk of AI viruses being transported to Europe through poultry trade is negligible as live poultry, day-old chicks and semen have been identified as the only non-wild bird pathways via which AI virus introduction is non-negligible, and as suitable risk management measures are in place, such as testing and quarantine (EFSA AHAW Panel et al, 2017).…”
Section: Scientific Analysis Of Ai Spread From Non-eu/eea Countries Tmentioning
confidence: 99%
“…Nevertheless, the risk of AI viruses being transported to Europe through poultry trade is negligible as live poultry, day-old chicks and semen have been identified as the only non-wild bird pathways via which AI virus introduction is non-negligible, and as suitable risk management measures are in place, such as testing and quarantine (EFSA AHAW Panel et al, 2017). Nevertheless, the risk of AI viruses being transported to Europe through poultry trade is negligible as live poultry, day-old chicks and semen have been identified as the only non-wild bird pathways via which AI virus introduction is non-negligible, and as suitable risk management measures are in place, such as testing and quarantine (EFSA AHAW Panel et al, 2017).…”
Section: Scientific Analysis Of Ai Spread From Non-eu/eea Countries Tmentioning
confidence: 99%
“…Information on the presence of LPAIV in organs, tissue, meat and eggs was retrieved via a search in the Web of Science for the period 2005-2015 using the search terms 'avian influenza' and meat or eggs as described in Sections F12 and F13 of the latest EFSA scientific opinion on avian influenza (EFSA AHAW Panel, 2017). An additional search was carried out for the period 1/1/2016-17/7/2018.…”
Section: Datamentioning
confidence: 99%
“…Prevalence values in wild bird populations were estimated at 0.2%, 2% and 6% in low medium and high prevalence scenarios ('EFSA AHAW Panel, 2017). According to EFSA's Scientific Opinion (2017) 'Experimental infections with LPAIV showed that a transient, low-level antibody response can be generated, which may be sufficient to provide partial protection against reinfection with viruses of the same subtype; it is less likely that the induced humoral response confers protection against heterologous reinfections.…”
Section: Wild Birdsmentioning
confidence: 99%
“…IAV evolve rapidly [1] and occasionally, once introduced into poultry, low pathogenicity avian influenza (LPAI) viruses (LPAIV) of the H5 or H7 subtypes from the wild bird reservoir can directly evolve into highly pathogenic avian influenza (HPAI) viruses (HPAIV) [2, 3]. Although infections by both viruses largely have the same host range, they cause different diseases in terms of virulence [4, 5] and hence result in different needs for control and surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike LPAI where the infection can be detected via the presence of either virus or antibodies since infected birds mostly recover, almost no HPAIV infected poultry will survive [5] and infection is mostly detected via testing sick or dead birds for virus. Also, during outbreaks, HPAIV has been shown to easily spread by proximity [3] while LPAIV often spreads through contact networks [6]. …”
Section: Introductionmentioning
confidence: 99%